Slowed reacquisition of a previously extinguished response: the effect of partial extinction in human contingency learning - López-Gutiérrez, Francisco José; Barberia, Itxaso; Vadillo, Miguel Ángel; Andrades, Ainhoa (My University, 2015)
Extinction is a very relevant learning phenomenon from an applied and theoretical point of view. Extinction-based therapies constitute the most widespread empirically validated treatment of anxiety disorders. However, they face an important limitation, as relapse often takes place once the extinction procedure has been completed. We provide the first demonstration of relapse reduction, a slowed reacquisition, in human contingency learning after a partial extinction procedure using mild aversive stimuli. This effect was specific of the partial extinction treatment (i.e., reinforced trials were occasionally experienced during extinction; Experiment 1) and not only due to differences in uncertainty levels between the partial and a standard extinction group (Experiment 2). Experiment 3 explored conditions in which partial extinction was complete, while the slowed reacquisition effect was still obtained. Potential uses of this strategy in anxiety disorders therapies, its theoretical explanation and its current limitations are discussed.
Keywords: Angustia; Psicoterapia; Associative learning; Extinction